(untitled) (Vallis Aurea, 2024)
Migration plays a pivotal role in the work culture of many lives. In most cases it creates a positive effect on the quality of work life of labourers especially in industrial sector. This positive vibe leads to an effective growth towards manufacturing sectors especially in plywood industries. In this paper the researcher tries to analyses the quality of work life of migrant workers in plywood industries and was surveyed migrant workers in Kerala, India. A pre-tested semi-structured questionnaire was used for the responds collection and a total of 250 migrant workers have been interviewed. From the study it was concluded that the migration process brought out significant changes to their quality of life.